2023
DOI: 10.1097/brs.0000000000004695
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs in the Acute Post-operative Period Are Associated With an Increased Incidence of Pseudarthrosis, Hardware Failure, and Revision Surgery Following Single-level Spinal Fusion

Abstract: Study Design. Retrospective study. Summary of Background Data. Research has shown that the use of NSAIDs and COX-2 inhibitors increases the risk of pseudoarthrosis following spinal fusion surgery. Pseudoarthrosis can lead to complications such as chronic pain and the need for additional surgeries. Objective. The purpose of this study was to examine the relationship between NSAID and COX-2 inhibitor use and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Combing with the anomeric proton signals at δ H 4.71 (1H, d, J = 1.2 Hz, H-1 ′′ ) and 5.65 (1H, d, J = 8. 4 Hz, H-1 ′ ), as well as the cross peaks shown in the 1 H 1 H COSY (Figure 2), the existence of α-L-rhamnopyranosyl and β-D-glucopyranosyl was clarified. In addition, the signals for methoxyl at δ H 3.91 (3H, s, 3-OCH 3 ), three aromatic protons with ABX spin coupling systems at δ H 6.86 (1H, d, J = 8.4 Hz, H-5), 7.62 (1H, d, J = 1.8 Hz, H-2), and 7.65 (1H, dd, J = 1.8, 8.4 Hz, H-6)] were detected by its 1 H NMR spectrum.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Combing with the anomeric proton signals at δ H 4.71 (1H, d, J = 1.2 Hz, H-1 ′′ ) and 5.65 (1H, d, J = 8. 4 Hz, H-1 ′ ), as well as the cross peaks shown in the 1 H 1 H COSY (Figure 2), the existence of α-L-rhamnopyranosyl and β-D-glucopyranosyl was clarified. In addition, the signals for methoxyl at δ H 3.91 (3H, s, 3-OCH 3 ), three aromatic protons with ABX spin coupling systems at δ H 6.86 (1H, d, J = 8.4 Hz, H-5), 7.62 (1H, d, J = 1.8 Hz, H-2), and 7.65 (1H, dd, J = 1.8, 8.4 Hz, H-6)] were detected by its 1 H NMR spectrum.…”
Section: Resultsmentioning
confidence: 88%
“…Clinical studies have demonstrated that prolonged use of steroidal anti-inflammatory drugs can result in osteoporosis in 50% of patients [ 3 ]. Non-steroidal anti-inflammatory drugs also exhibit notable adverse reactions, including peptic ulcers, renal failure, and cardiovascular diseases [ 4 ]. Traditional Chinese medicine (TCM) has garnered significant attention from researchers due to its remarkable efficacy and minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation